PENGARUH MODEL KOOPERATIF TGT BERBANTUAN BAAMBOOZLE TERHADAP HASIL BELAJAR KOGNITIF IPAS KELAS V SDN DURBUK 2 PAMEKASAN - Fatimah Azzahroh; Ade Cyntia Pritasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether there is a significant effect of the TGT cooperative learning model, supported by Baamboozle, on the science learning outcomes of fifth-grade students at SDN Durbuk 2 Pamekasan in the 2025/2026 academic year. This study employed a quantitative method with a pre-experimental design and a one-group pretest-posttest model. The population consisted of all fifth-grade students, totaling 22 students. The sampling technique used was a saturated sample. The results of the study indicate that 1) Students’ learning outcomes improved after the implementation of the TGT cooperative learning model assisted by Baamboozle, as evidenced by the average pretest score of 55.00 increasing to 81.36 on the posttest. 2) The results of the hypothesis test using a paired-sample t-test yielded a significance value (Sig. 2-tailed) of 0.000 < 0.05 and a calculated T-value of 10.163 > the critical T-value of 2.079; thus, it can be concluded that there is a significant effect of the implementation of the TGT cooperative learning model assisted by Baamboozle on the learning outcomes of Grade 5 IPAS students at SDN Durbuk 2 Pamekasan. 3) The implementation of the Baamboozle-assisted TGT cooperative learning model in learning activities that took place over two sessions was carried out well, with an average teacher activity score of 95.2% in the “very good” category and an average student activity score of 86.8% in the “very good” category.